An enhanced level of VCAM in transplant preservation fluid is an independent predictor of early kidney allograft dysfunction - Baboudjian, Michael; Gondran-Tellier, Bastien; Boissier, Romain; Ancel, Patricia; Marjollet, Juline; Lyonnet, Luc; François, Pauline; Sabatier, Florence; Lechevallier, Eric; Dutour, Anne; Paul, Pascale (Frontiers in Immunology, 2022)
Background We aimed to evaluate whether donor-related inflammatory markers found in kidney transplant preservation fluid can associate with early development of kidney allograft dysfunction. Methods Our prospective study enrolled 74 consecutive donated organs who underwent kidney transplantation in our center between September 2020 and June 2021. Kidneys from 27 standard criteria donors were allocated to static cold storage and kidneys from 47 extended criteria donors to hypothermic machine perfusion. ELISA assessment of inflammatory biomarkers (IL-6, IL6-R, ICAM, VCAM, TNFα, IFN-g, CXCL1 and Fractalkine) was analyzed in view of a primary endpoint defined as the occurrence of delayed graft function or slow graft function during the first week following transplantation. Results Soluble VCAM levels measured in transplant conservation fluid were significantly associated with recipient serum creatinine on day 7. Multivariate stepwise logistic regression analysis identified VCAM as an independent non-invasive predictor of early graft dysfunction, both at 1 week (OR: 3.57, p = .04, 95% CI: 1.06-12.03) and 3 Months (OR: 4.039, p = .034, 95% CI: 1.11-14.73) after transplant surgery. Conclusions This prospective pilot study suggests that pre-transplant evaluation of VCAM levels could constitute a valuable indicator of transplant health and identify the VCAM-CD49d pathway as a target to limit donor-related vascular injury of marginal transplants.